Implicit Recognition of Familiar and Unfamiliar Faces in Schizophrenia: A Study of the Skin Conductance Response in Familiarity Disorders - Ameller, Aurely; Picard, Aline; D’Hondt, Fabien; Vaiva, Guillaume; Thomas, Pierre; Pins, Delphine (Frontiers in Psychiatry, 2017)
Objective: Familiarity is a subjective sensation that contributes to person recognition. This process is described as an emotion-based memory-trace of previous meetings and could be disrupted in schizophrenia. Consequently, familiarity disorders could be involved in the impaired social interactions observed in patients with schizophrenia. Previous studies have primarily focused on famous people recognition. Our aim was to identify underlying features, such as emotional disturbances, that may contribute to familiarity disorders in schizophrenia. We hypothesize that patients with familiarity disorders will exhibit a lack of familiarity that could be detected by a flattened skin conductance response. Method: The skin conductance response was recorded to test the hypothesis that emotional reactivity disturbances occur in patients with schizophrenia during the categorization of specific familiar, famous and unknown faces as male or female. Forty-eight subjects were divided into the following 3 matched groups with 16 subjects per group: control subjects, schizophrenic people with familiarity disorder and schizophrenic people without familiarity disorders. Results: Emotional arousal is reflected by the skin conductance measures. The control subjects and the patients without familiarity disorders experienced a differential emotional response to the specific familiar faces compared with that to the unknown faces. Nevertheless, overall, the schizophrenic patients without familiarity disorders showed a weaker response across conditions compared with the control subjects. In contrast, the patients with familiarity disorders did not show any significant differences in their emotional response to the faces, regardless of the condition. Conclusions: Only patients with familiarity disorders fail to exhibit a difference in emotional response between familiar and non-familiar faces. These patients likely emotionally process familiar faces similarly to unknown faces. Hence, the lower feelings of familiarity in schizophrenia may be a premise enabling the emergence of familiarity disorders.